Effect of oxygenated polyethylene glycol decorated hemoglobin on microvascular diameter and functional capillary density in the transgenic mouse model of sickle cell anemia. (February 2015) - Tsai, Amy G.; Cabrales, Pedro; Young, Mark A.; Winslow, Robert M.; Intaglietta, Marcos
Abstract Malemide polyethylene glycol-conjugated Hb (MP4OX, Sangart Inc.), a high-affinity low-concentration acellular hemoglobin (P50 = 5 mmHg, 4.3 g/dl) solution, has been shown to optimize microvascular perfusion and target oxygen delivery to anoxic tissue. Microvascular perfusion during an acute hypoxic challenge in a transgenic anemic sickle cell disease mouse model was studied with MP4OX and saline. Arterioles were dilated in both groups. Functional capillary density (FCD) was maintained at a higher level with MP4OX. In conclusion, MP4OX treatment reduced the hypoxia-mediated decline in FCD, an effect in part due to higher arterial pressure resulting in increased microvascular perfusion pressures.